Intraoperative Torque Test to Assess Syndesmosis Instability. (April 2019) - Gosselin-Papadopoulos, Nayla; Hébert-Davies, Jonah; Laflamme, G. Yves; Beauséjour, Marie; Ménard, Jérémie; Leduc, Stéphane; Nault, Marie-Lyne
Background: In this cadaveric study, a new "torque test" (TT) stressing the fibula posterolaterally under direct visualization was compared with the classical external rotation stress test (ERT) and lateral stress test (LST). Methods: The anteroinferior tibiofibular ligament (AiTFL), the interosseous membrane (IOM), and the posteroinferior tibiofibular ligament (PiTFL) were sectioned sequentially on 10 fresh-frozen human ankles. At each stage of dissection, instability was assessed using the LST, ERT, and TT under direct visualization. Anatomical tibiofibular diastasis measurements were taken directly on cadavers and compared using the Wilcoxon signed rank test. Results: All 3 tests showed statistically significant motion in the syndesmosis when at least 2 ligaments were sectioned. The mean increase across diastasis with a 2-ligament section was 3.0 mm ( P = .005), 3.2 mm ( P = .005), and 4.8 mm ( P = .005) for the LST, ERT, and TT, respectively. The largest mean increase in diastasis was obtained with a complete injury using the TT and was 6.2 mm ( P = .008). With the TT, a 3.5-mm tibiofibular diastasis was 90% sensitive and 100% specific when 2 or more syndesmotic ligaments were sectioned. Conclusion: The TT was a more sensitive and specific tool for detecting syndesmosis instability than classic LST and ERT. Clinical relevance: Stressing the fibula in a posterolateral direction created a larger distal tibiofibular diastasis, which would be easier to detect in the intraoperative setting. The TT was more sensitive and specific to detecting a 2-ligament syndesmotic injury than the classic test and required less force to perform.